Desperately seeking certainty the misguided quest for constitutional foundations - Farber, Daniel A., 1950-; Sherry, Suzanna (Chicago, [Ill.] : University of Chicago Press, 2002)
'Desperately Seeking Certainty' attacks the current legal vogue for grand unified theories of constitutional interpretation. On both the Right and the Left, prominent legal scholars are attempting to build all of constitutional law from a single foundational idea. Dan Farber and Suzanna Sherry find that in the end no single, all-encompassing theory can successfully guide judges or provide definitive or even sensible answers to every constitutional question.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constitutional law -- United States; Constitutional law -- United States -- Philosophy; Law; United States of America, USA; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general